Minute‐Scale Adsorption of Diverse Marine Viruses Onto Clay Minerals - Lanlan Cai; Yuan Tian; Xuan Qiu; Yongle Xu; Hailiang Dong; Rui Zhang (Environmental Microbiology, 2026)
Viruses are ubiquitous biological entities with important roles in microbial mortality, genetic exchange and biogeochemical cycles. Clays, the most abundant mineral constituents on Earth, function as highly effective adsorbents for viruses, critically modulating their environmental persistence and ecological impact. However, the mechanisms and environmental drivers governing virus–clay interactions remain poorly understood. This study systematically investigates the adsorption kinetics of nine marine viruses onto a clay mineral (smectite, NAu‐2) under environmentally representative conditions. Viruses isolated from distinct hosts (heterotrophic bacteria, cyanobacteria and eukaryotic algae) and exhibiting diverse morphological features (myovirus, siphovirus, podovirus and tailless virus) were evaluated across gradients of NAu‐2/virus concentrations, pH, temperature and ionic strength. Elevated NAu‐2 concentrations (> 50 mg/L) induced rapid and near‐complete virus adsorption (90%–99%) within 1 min, while low concentrations (0.1–10 mg/L) yielded efficiencies from negligible to > 50%. Adsorption dynamics showed minimal correlation with viral morphology and instead depended on physicochemical properties. Electron microscopy revealed preferential viral localization at edge sites of NAu‐2, driven by charge heterogeneity from protonated alumina‐oxygen octahedra. These findings provide quantitative information on virus–clay interactions and offer key insights into the availability, transport and fate of viruses in the environment, paving the way for more accurate parameterization of biogeochemical cycling across ecosystems.

Phylogenetic distance–decay patterns are not explained by local community assembly processes in freshwater lake microbial communities - Yian Gu; Zhidan Li; Peng Lei; Rui Wang; Hong Xu; Ville‐Petri Friman (Environmental Microbiology, 2023)
While water and sediment microbial communities exhibit pronounced spatio‐temporal patterns in freshwater lakes, the underlying drivers are yet poorly understood. Here, we evaluated the importance of spatial and temporal variation in abiotic environmental factors for bacterial and microeukaryotic community assembly and distance–decay relationships in water and sediment niches in Hongze Lake. By sampling across the whole lake during both Autumn and Spring sampling time points, we show that only bacterial sediment communities were governed by deterministic community assembly processes due to abiotic environmental drivers. Nevertheless, consistent distance–decay relationships were found with both bacterial and microeukaryotic communities, which were relatively stable with both sampling time points. Our results suggest that spatio‐temporal variation in environmental factors was important in explaining mainly bacterial community assembly in the sediment, possibly due lesser disturbance. However, clear distance–decay patterns emerged also when the community assembly was stochastic. Together, these results suggest that abiotic environmental factors do not clearly drive the spatial structuring of lake microbial communities, highlighting the need to understand the role of other potential drivers, such as spatial heterogeneity and biotic species interactions.

Nitrogen repression of deoxynivalenol biosynthesis is mediated by Mep2 ammonium permease in Fusarium graminearum - Yuting Hu; Rui Hou; Zeyi Wang; Weiwei Zhang; Jin‐Rong Xu (Environmental Microbiology, 2022)
Fusarium graminearum is an important wheat pathogen and a producer of deoxynivalenol (DON). Biosynthesis of DON is suppressed by ammonium and induced by arginine and polyamines. To better understand ammonium repression of DON biosynthesis, in this study, we functionally characterized three ammonium permease ( MEP ) genes in F. graminearum . All the mep deletion mutants were normal in growth on V8 agar. Whereas deletion of MEP1 had no detectable phenotypes, the mep2 and mep3 mutants had defects in hyphal growth under ammonium limiting conditions and infection of wheat heads, with the latter having less severe defects. Deletion of MEP2 but not MEP3 affected nitrogen repression of DON biosynthesis and genes involved in nitrate metabolism. The mep2 mep3 double mutant had more severe defects in nitrogen repression than the mep2 mutant and was defective in ascospore releasing. Mutant alleles of MEP2 with truncated C‐terminal cytoplasmic tail (CT) failed to complement the mep2 mutant. Expression of a dominant active allele of RAS2 partially rescued the defects of mep2 in nitrogen repression. Taken together, these results suggest that Mep2 acts as the major sensor of ammonium availability in F. graminearum and its CT region functions in nitrogen repression via RAS2 and downstream signalling pathways.

Metabolic potentials of members of the class Acidobacteriia in metal‐contaminated soils revealed by metagenomic analysis - Rui Xu; Xiaoxu Sun; Max M. Häggblom; Yiran Dong; Miaomiao Zhang; Zhaohui Yang; Enzong Xiao; Tangfu Xiao; Pin Gao; Baoqin Li; Weimin Sun (Environmental Microbiology, 2022)
Summary The relative abundance of Acidobacteriia correlated positively with the concentrations of arsenic (As), mercury (Hg), chromium (Cr), copper (Cu) and other metals, suggesting their adaptation of the metal‐rich environments. Metagenomic binning reconstructed 29 high‐quality metagenome‐assembled genomes (MAGs) associated with Acidobacteriia , providing an opportunity to study their metabolic potentials. These MAGs contained genes to transform As, Hg and Cr through oxidation, reduction, efflux and demethylation, suggesting the potential of Acidobacteriia to transform such metal(loid)s. Additionally, genes associated with alleviation of acidic and metal stress were also detected in these MAGs. Acidobacteriia may have the capabilities to resist or transform metal(loid)s in acidic metal‐contaminated sites. Moreover, these genes encoding metal transformation could be also identified in the Acidobacteriia ‐associated MAGs from five additional metal‐contaminated sites across Southwest China, as well as Acidobacteriia ‐associated reference genomes from the NCBI database, suggesting that the capability of metal transformation may be widespread among Acidobacteriia members. This discovery provides an understanding of metabolic potentials of the Acidobacteriia in acidic metal‐rich sites.

The substrate‐dependent regulatory effects of the AfeI /R system in Acidithiobacillus ferrooxidans reveals the novel regulation strategy of quorum sensing in acidophiles - Xue‐Yan Gao; Chang‐Ai Fu; Likai Hao; Xiu‐Feng Gu; Rui Wang; Jian‐Qiang Lin; Xiang‐Mei Liu; Xin Pang; Cheng‐Jia Zhang; Jian‐Qun Lin; Lin‐Xu Chen (Environmental Microbiology, 2021)
Summary A LuxI/R‐like quorum sensing (QS) system (AfeI/R) has been reported in the acidophilic and chemoautotrophic Acidithiobacillus spp. However, the function of AfeI/R remains unclear because of the difficulties in the genetic manipulation of these bacteria. Here, we constructed different afeI mutants of the sulfur‐ and iron‐oxidizer A . ferrooxidans , identified the N‐acyl homoserine lactones (acyl‐HSLs) synthesized by AfeI, and determined the regulatory effects of AfeI/R on genes expression, extracellular polymeric substance synthesis, energy metabolism, cell growth and population density of A . ferrooxidans in different energy substrates. Acyl‐HSLs‐mediated distinct regulation strategies were employed to influence bacterial metabolism and cell growth of A . ferrooxidans cultivated in either sulfur or ferrous iron. Based on these findings, an energy‐substrate‐dependent regulation mode of AfeI/R in A . ferrooxidans was illuminated that AfeI/R could produce different types of acyl‐HSLs and employ specific acyl‐HSLs to regulate specific genes in response to different energy substrates. The discovery of the AfeI/R‐mediated substrate‐dependent regulatory mode expands our knowledge on the function of QS system in the chemoautotrophic sulfur‐ and ferrous iron‐oxidizing bacteria, and provides new insights in understanding energy metabolism modulation, population control, bacteria‐driven bioleaching process, and the coevolution between the acidophiles and their acidic habitats.

QsvR integrates into quorum sensing circuit to control Vibrio parahaemolyticus virulence - Yiquan Zhang; Linghui Hu; Yue Qiu; George Osei‐Adjei; Hao Tang; Ying Zhang; Rui Zhang; Xiumei Sheng; Shungao Xu; Wenhui Yang; Huiying Yang; Zhe Yin; et al. (Environmental Microbiology, 2019)
Summary Vibrio parahaemolyticus , the leading cause of seafood‐associated gastroenteritis worldwide, requires the two type‐III secretion systems (T3SS1 and T3SS2) and a thermostable direct hemolysin (encoded by tdh1 and tdh2 ) for full virulence. The tdh genes and the T3SS2 gene cluster constitute an 80 kb pathogenicity island known as Vp‐PAI located on the chromosome II. Expression of T3SS1 and Vp‐PAI is regulated in a quorum sensing (QS)‐dependent manner but its detailed mechanisms remain unknown. Herein, we show that three factors (QS regulators AphA and OpaR and an AraC‐type transcriptional regulator QsvR) form a complex regulatory network to control the expression of T3SS1 and Vp‐PAI genes. At low cell density (LCD), whereas Vp‐PAI expression is repressed, T3SS1 genes are induced by AphA, which directly binds (an operator region of) the exsBAD‐vscBCD operon. At high cell density (HCD), the bacterium turns off T3SS1 expression by replacing AphA with OpaR, triggering the induction of Vp‐PAI. Furthermore, QsvR binds to the regulatory regions of all the tested T3SS1 and Vp‐PAI genes to activate their transcription at HCD. Taken together, our data highlight how multiple QS regulators contribute to the pathogenicity of V. parahaemolyticus by precisely controlling the expression of major virulence determinants during different stages of growth.

Novel phage–host interactions and evolution as revealed by a cyanomyovirus isolated from an estuarine environment - Yongle Xu; Rui Zhang; Nannan Wang; Lanlan Cai; Yigang Tong; Qiang Sun; Feng Chen; Nianzhi Jiao (Environmental Microbiology, 2018)
Summary Cyanophages are thought to affect the community structure, population dynamics, metabolic activity and evolution of picocyanobacteria and to impact the biogeochemical cycling in aquatic ecosystems. Here, we report an estuarine Synechococcus phage, S‐CBWM1, which represents a novel viral lineage and exhibits interesting genetic features related to phage–host interactions and evolution. S‐CBWM1 encapsidates four virion‐associated proteins related to cellular metabolic regulation. Several novel auxiliary metabolic genes related to multidrug efflux, cell wall and capsule synthesis or modifications were also identified. In addition, the presence of the largest number of tRNA genes hitherto found in a phage genome may contribute to the translation efficiency of unique genes. These genomic and proteomic features of S‐CBWM1 suggested phage–host interactions involved in adaptation to eutrophic estuarine environments. Phylogenetic and metagenomic analysis of the pol γ gene in the S‐CBWM1 genome provided new insights into the evolutionary path of mitochondrial DNA polymerase gamma. The S‐CBWM1 psbA contains two group I introns, representing the first instance of multiple introns within psbA from phage. The isolation of S‐CBWM1 reveals that estuarine ecosystems contain evolutionarily novel cyanophages that drive unique phage–host interactions.

TRI6 and TRI10 play different roles in the regulation of deoxynivalenol (DON) production by cAMP signalling in Fusarium graminearum - Cong Jiang; Chengkang Zhang; Chunlan Wu; Panpan Sun; Rui Hou; Huiquan Liu; Chenfang Wang; Jin‐Rong Xu (Environmental Microbiology, 2016)
Summary The biosynthesis of mycotoxin deoxynivalenol (DON) in Fusarium graminearum is regulated by two pathway‐specific transcription factors Tri6 and Tri10 and affected by various host and environmental factors. In this study, we showed that cyclic adenosine monophosphate (cAMP) treatment induced DON production by stimulating TRI gene expression and DON‐associated cellular differentiation in F. graminearum . Interestingly, exogenous cAMP had no effects on the tri6 mutant but partially recovered the defect of tri10 mutant in DON biosynthesis. Although the two cAMP phosphodiesterase genes PDE1 and PDE2 had overlapping functions in vegetative growth, conidiation, sexual reproduction and plant infection, deletion of PDE2 but not PDE1 activated intracellular PKA activities and increased DON production. Whereas the tri6 pde2 mutant failed to produce DON, the tri10 pde2 double mutant produced a significantly higher level of DON than the tri10 mutant. Cellular differentiation associated with DON production was stimulated by exogenous cAMP or deletion of PDE2 in both tri10 and tri6 mutants. These data indicate that TRI6 is essential for the regulation of DON biosynthesis by cAMP signalling but elevated PKA activities could partially bypass the requirement of TRI10 for TRI gene‐expression and DON production, and Pde2 is the major cAMP phosphodiesterase to negatively regulate DON biosynthesis in F. graminearum .